The future of leadership development : corporate needs and the role of business schools - Canals, Jordi (New York : Palgrave Macmillan, 2011)
"The current financial crisis highlights the need to rethink business leadership and the role of business schools in helping firms develop the leaders of the future. This book brings together the perspectives of deans of top international business schools, and the views of CEOs and senior business leaders"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Leadership; Business education; Business schools; Business and economics